Strategi Peningkatan Prestasi Belajar Sintaksis Mahasiswa Program Studi Pendidikan Bahasa Indonesia FKIP Universitas Bengkulu dengan Metode Brainstorming - Rokhmat Basuki; Suryadi Suryadi (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2019)
This study aims to describe the syntactic learning process and find out the improvement of syntactic lecture achievement by using the brainstorming method in the students of the Indonesian Language Study Program at FKIP Bengkulu University. The research method uses classroom action research methods. Data collection techniques using tests, interviews, and observations. The research subjects were students in the IVC semester of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Bengkulu University. Data analysis techniques were carried out utilizing data reduction, data presentation, interpretation of test analysis results, interviews, and observations, and making conclusions based on indicators of success in classroom action research. The results showed that there were changes in students' attitudes and behaviors that were more positive. In the first cycle, students look happy and excited in lectures. Besides, in the second cycle, students were increasingly active and enthusiastic in participating in the whole series of lectures. Lecture achievements obtained by students in the category increased with satisfying results. Proven in the first cycle, the average value of 70 students with details of 7 students who get excellent grades or 19%. Students with good grades are 19 or 53%. Then, students with sufficient grades of 10 or 28%. Whereas in the second cycle the achievement of an average score of 78.5 with the details of 12 students got excellent grades or 33%, while students who got good grades were 24 students or 67%.